Towards real time in-vivo rectal dosimetry during trans-rectal ultrasound based high dose rate prostate brachytherapy using MOSkin dosimeters. (October 2020) - Poder, Joel; Howie, Andrew; Brown, Ryan; Bucci, Joseph; Rosenfeld, Anatoly; Enari, Komiti; Schreiber, Kristine; Carrara, Mauro; Bece, Andrej; Malouf, David; Cutajar, Dean
Highlights: In-vivo rectal dosimetry for 20 HDR prostate brachytherapy fractions with MOSkins. The average per fraction MOSkin doses agree with TPS to within −1.6% ± 11.1% ( k = 1). The average per catheter MOSkin doses agree with TPS to within +2.5% ± 16.9% ( k = 1). Uncertainty dominated by localisation of the MOSkins within reference frame of TPS. 64% of per catheter MOSkin doses agreed with TPS within uncertainty of 11.5%. Abstract: Purpose: To compare the dose measured by MOSkin dosimeters coupled to a trans-rectal ultrasound (TRUS) probe to the dose predicted by the brachytherapy treatment planning system (BTPS) during high dose rate (HDR) prostate brachytherapy (pBT), and to examine the feasibility of performing real-time catheter-by-catheter analysis of in-vivo rectal dosimetry during TRUS based HDR pBT. Method: Four MOSkin dosimeters were coupled to a TRUS probe during 20 TRUS-based HDR pBT treatment fractions. The measured MOSkin doses were retrospectively compared to those predicted by the BTPS for the total treatment fraction, as well as on a per catheter basis. Results: The average relative percentage difference between MOSkin measured and BTPS predicted doses for a total treatment fraction was 0.3% ± 11.6% ( k = 1), with a maximum of 23.2% and a minimum of −29.0%. The average relative percentage difference per catheter was +2.5% ± 16.9% ( k = 1). The majority (64%) of per catheter MOSkin measured doses agreed with the treatment planning system within the calculated uncertainty budget of 12.3%. Conclusion: The results of the study agreed well with previously published data, despite differences in clinical workflows. To improve the redundancy to potential dosimeter errors, a minimum of 4 MOSkin dosimeters should be used when performing real-time in-vivo rectal dosimetry for HDR pBT, and error thresholds should be based off the total combined uncertainty estimate of measurement. 'Real time' error thresholds can be more confidently applied in the future through enhanced integration between IVD systems with both the imaging device and the BTPS/afterloader.